Creación de una empresa productora y comercializadora de manjar de papa, cantón Valencia en el año 2014 - Vera Bravo, Elicenia Guadalupe (2015)
The present research on the business plan for the implementation of a producer and marketer of delicacy Pope in Valencia Canton, was held in the canton of the same name, Provincia de Los Rios, with which the inhabitants of this sector will be presented as a new product, excellent quality can compete with any similar product and meet the demands and needs of consumers. To do a market study where it was known product acceptance, intention with which projected demand, the ability to attend to by the company, establishing the technical and administrative requirements leading to an economic analysis. The market is oriented to know what quality standards and requirements necessary to require potential consumers to purchase the product are Papa delicacy…..